Keragaan Usaha Tani Tembakau Dalam Penggunaan Varietas Unggul Lokal di Kecamatan Wangon, Kabupaten Banyumas - Reni Kristyanti; Dindy Darmawati Putri; Djeimy Kusnaman (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2025)
The large number of small-scale farmers presents a significant barrier to agricultural development, particularly in plantation commodities that require effective and adaptive farming management practices. The utilization of superior local varieties is essential for sustaining productivity and averting failures in the tobacco industry under these conditions. This study analyzed the performance of tobacco farming among small-scale farmers utilizing superior local varieties in Wangon District, Banyumas Regency. The research was carried out between January and May 2025, utilizing a survey methodology. Seventy tobacco farmers with land areas of less than 0.5 hectares were selected purposefully. Data were collected via interviews and field observations and subsequently analyzed descriptively. The findings indicate that tobacco farming typically serves as a supplementary activity alongside their main occupation of rice farming. Many large farmers possess over 20 years of agricultural experience and exhibit comparatively low levels of formal education. The primary local superior varieties used are the Genjah Kenanga and Genjah Bojong varieties. The average productivity of dry tobacco was 868 kg/ha, with a selling price of Rp 70,000/kg, resulting in an average income of Rp 9,285,000/ha per planting season. Farmers select local superior varieties due to their shorter lifespan, ease of maintenance, adaptability to local environmental conditions, and provision of more stable market access and pricing. The findings suggest that local superior varieties may enhance tobacco farming for smallholder farmers.